Evidence for ice-free summers in the late Miocene central Arctic Ocean - Ruediger Stein (Nature Portfolio, 2016)
Despite the importance of Arctic sea-ice in the global climate system, a paucity of pre-Quaternary sedimentary archives limits our understanding of its long-term history. Here, based on ancient sediments revealed by submarine landslides, the authors reconstruct Arctic sea-ice conditions during the Miocene.